Are Ethical Banks Different? A Comparative Analysis Using the Radical Affinity Index - San-Jose, Leire; Retolaza, Jose Luis; Gutierrez-Goiria, Jorge (2011)
This article studies the differences between traditional financial intermediaries (commercial banks, savings banks and cooperative banks) and ethical banks based on property rights, in which the owner decides the ideology, principles, standards and objectives of the organisation. In ethical banking, affinity centres on positive social and ethical values. The article consequently focuses on an index proposed both to differentiate ethical banks from other types of banks, and also to pinpoint the differences between the various ethical banks themselves. This is the Radical Affinity Index (RAI), which groups banks together in terms of their stance on ethical commitment, concentrating on ethical ideology and principles (information transparency, placement of assets, guarantees and participation) and using a sample of 114 European banks. The evidence shows that transparency of information and placement of assets are factors that differentiate ethical banks from other financial intermediaries. Guarantees and participation are characteristics specific to ethical banks; these variables, however, do not offer clear evidence to our analysis.
Keywords: Transparency; Ranking; Radical Affinity Index; Participation; guarantees; Ethical banking; assets placement